1991
DOI: 10.1029/91ja00446
|View full text |Cite
|
Sign up to set email alerts
|

On large‐scale rotational motions and energetics of auroral shear layers

Abstract: The stability, dynamics and energetics of an auroral shear layer are considered in the framework of incompressible, one‐fluid magnetohydrodynamics, under conditions where current flow through the system is limited by the finite Pedersen conductivity and an enhanced field‐aligned resistivity. The model includes a magnetospheric region where currents resulting from polarization electric fields and viscous forces are important, an ionospheric substrate of uniform conductivity, and a force‐free acceleration region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Previous electrostatic models studying the stability of the velocity shear layer in the M-I coupling system included the ionospheric coupling, but they are not fully 3-D, because the magnetosphere is either height-integrated [Keskinen et al, 1988] or a current-voltage relationship has been used [Lotko andShen, 1991' Wei andLee, 1993].…”
Section: Introductionmentioning
confidence: 99%
“…Previous electrostatic models studying the stability of the velocity shear layer in the M-I coupling system included the ionospheric coupling, but they are not fully 3-D, because the magnetosphere is either height-integrated [Keskinen et al, 1988] or a current-voltage relationship has been used [Lotko andShen, 1991' Wei andLee, 1993].…”
Section: Introductionmentioning
confidence: 99%
“…FACs and found that the potential profile corresponds to observed inverted V events. The two-dimensional model for the nonsteady boundary layer flow dynamics including the ionospheric drag and a parallel electric field was also developed [Lotko et al, 1987;Lotko and Shen, 1991]. Lotko et al [1987] showed that the sheared plasma flow couples to the polar ionosphere and may be responsible for the formation of V shocks in and above the auroral acceleration region.…”
mentioning
confidence: 99%
“…Lotko et al [1987] showed that the sheared plasma flow couples to the polar ionosphere and may be responsible for the formation of V shocks in and above the auroral acceleration region. The stability, dynamics, and energetics of an auroral shear layer are studied by Lotko and Shen [1991]. Nonlinear evolution of the KH instability in the polar ionosphere due to the sheared plasma flow in the magnetosphere including the finite Pedersen conductivity has also been studied [Keskinen et al, 1988].…”
mentioning
confidence: 99%
“…The electrostatic Kelvin‐Helmholtz (KH) instability has been very often invoked as a possible mechanism for the auroral deformations [e.g., Hallinan and Davis , 1970; Miura and Sato , 1978; Wagner et al , 1983; Murphree et al , 1994; Yamamoto et al , 1994]. For realistic modeling, proper attention should be paid to the effect of the ionospheric Pedersen conductivity coupling [e.g., Lotko et al , 1987; Keskinen et al , 1988; Lotko and Shen , 1991; Wei and Lee , 1993; Lysak et al , 1995]. Particularly, Keskinen et al showed a stability criterion to the auroral phenomena in the plasma sheet: the outer plasma sheet is likely to be unstable to the KH instability because the inertial relaxation rate v is usually smaller than the shear frequency, while the inner part is stable because of v exceeding the shear frequency.…”
Section: Introductionmentioning
confidence: 99%